Application of multidetector computed tomography in the diagnosis of pulmonary embolism and new directions of development - Pałka, Justyna; Leśniewska, Aleksandra; Przybylski, Piotr (Journal of Education, Health and Sport, 2019)
Introduction: Pulmonary embolism (PE) is a condition involving the mechanical part of the closure of the pulmonary arterial thrombus or other embolic material. Is the third the most typical cardiovascular disease - vascular, immediately after a heart attack and stroke. Clinical symptoms are often nonspecific and may result in an incorrect diagnosis. The most common complications of PE include: attack the lungs, impaired heart function, superinfection and development of pulmonary hypertension.Objective: The purpose of the work was to discuss of the technical aspects and the use of multi-slice computed tomography in the diagnosis of PE. The presentation emphasized new directions of development of tomographic methods in imaging thromboembolic events of pulmonary arteries, including multi-energy CT and low-dose techniques.Description of the state of knowledge: Angiography-CT is currently the gold standard in the diagnosis of PE, especially in patients with high and indirect clinical risk. It is characterized by high sensitivity and specificity in contrast enhancement imaging defects within the pulmonary vasculature and blood changes in the pulmonary parenchyma, which may accompany the EP. It also allows to assess the features of right heart overload in the course of massive PE or radiological symptoms associated with the development of chronic PE. Summary: Nowadays, the greatest challenges of CT diagnostics in PE are the improvement of image quality, minimization of artifacts and reduction of the radiation dose to which the patient is exposed. Effective diagnosis of PE is not only good quality CT imaging, but also the efficiency of the process of diagnosis. Hence the development of new applications of CT - called. computer aided diagnosis (CAD).